Bauchi State Agricultural Development Project (Bauchi: Bauchi State Agricultural Development Project, 1980)
The Bauchi State Agricultural Development Project (BSADP) has been established by the Federal and Bauchi State Governments with the objective of improving the production of essential food crops and raising farm family income
osc 21/05/2019
Arch
Keywords: Agricultural economics; Agricultural production; Nigeria